Antibiotic resistance characteristics and risk factors analysis of Helicobacter pylori strains isolated from patients in Liaoning Province, an area in North China - Wang, Yanmeng; Li, Yiling; Gong, Yuehua; Dong, Yuzhen; Sun, Jing; Chen, Moye (PeerJ, 2023)
Background The prevalence of Helicobacter pylori (H. pylori) keeps rising while the eradication rate continues to decline due to the increasing antibiotic resistance. Regional variations of antimicrobial resistance to H. pylori have been recommended by guidelines in recent years. This study aims to investigate the antibiotic resistance rate of H. pylori and its association with infected subjects’ characteristics in Liaoning Province, an area in north China. Methods Gastric tissues from 178 H. pylori positive participants without previous antibiotic use within four weeks were collected for H. pylori culture. Antibiotic susceptibility to furazolidone (AOZ), tetracycline (TC), levofloxacin (LFX), metronidazole (MET), clarithromycin (CLA), and amoxicillin (AMX) were examined with the agar dilution method. Associations between H. pylori resistance and patient characteristics were further analysed. Results No resistance was observed in AOZ or TC. For LFX, MET, CLA, and AMX, the overall resistance rates were 41.10%, 79.14%, 71.78%, and 22.09% respectively. There were significant differences between resistance to CLA and MALToma (P = 0.021), and between resistance to MET and age (P < 0.001). Conclusions The primary resistant rates of LEX, MET, CLA, and AMX were relatively high in Liaoning. Treatment effectiveness improvement could be achieved by prior antimicrobial susceptibility tests before antibiotic prescription.
Keywords: Helicobacter pylori; Antibiotic resistance; Eradication; Multi-resistance; Regional characteristic; Liaoning Province